Strategi Lembaga Pengembangan Pengkajian Al Islam dan Kemuhammadiyahan (LPPAIK) dalam mengintegrasikan ilmu terhadap Nilai-nilai Islam - Hannan, Ahmad Affan; Purwidianto, Purwidianto (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The integration of Islamic knowledge is a process and programmatic process that comes in the form of Islamic principles and comes out, namely humans with an Islamic personality, Islamic knowledge and Islamic morals. The separation of Islam influences people's behavior towards the development of science. The Al Islam Kemuhammadiyahan Institute (LPPAIK) plays a central role in bridging the gap between general knowledge and Islamic teachings. LPPAIK aligns general knowledge or science with Islamic values ​​and views its main mission as the development of individuals who are able to navigate the complexities of the modern world while adhering to Islamic principles. This research aims to identify institutional policies in implementing Islamic and Muhammadiyah values, analyze the process of implementing Islamic values ​​in learning, assess the effectiveness of policies for internalizing Islamic values, determine human resources and supporting facilities, analyze collaboration with external institutions at Muhammadiyah University Prof. Dr. Hamka. This research is a field study with a qualitative approach, by examining field data sources and documentary research from various scientific journals, and using direct observation, interviews and documentation methods. The informants for this research are leaders/staff/educators or people associated with the Muhammadiyah University Prof. Dr. Hamka. By finding out to what extent these values ​​are implemented, the final aim of this research is to serve as a starting point for universities, especially in reforming their education curriculum into a curriculum that internalizes these values ​​in all learning in courses or other activities.